Continuous delivery of propranolol from liposomes-in-microspheres significantly inhibits infantile hemangioma growth - Guo XN (Dove Medical Press, 2017)
Xiaonan Guo,1,* Xiaoshuang Zhu,1,* Dakan Liu,1 Yubin Gong,1 Jing Sun,2 Changxian Dong1 1Department of Hemangioma and Vascular Malformation, Henan Provincial People’s Hospital, Zhengzhou, People’s Republic of China; 2Department of Pharmacy, Second Military Medical University, Shanghai, People’s Republic of China *These authors contributed equally to this work Purpose: To reduce the adverse effects and high frequency of administration of propranolol to treat infantile hemangioma, we first utilized propranolol-loaded liposomes-in-microsphere (PLIM) as a novel topical release system to realize sustained release of propranolol.Methods: PLIM was developed from encapsulating propranolol-loaded liposomes (PLs) in microspheres made of poly(lactic-co-glycolic acid)-b-poly(ethylene glycol)-b-poly(lactic-co-glycolic acid) copolymers (PLGA-PEG-PLGA). The release profile of propranolol from PLIM was evaluated, and its biological activity was investigated in vitro using proliferation assays on hemangioma stem cells (HemSCs). Tumor inhibition was studied in nude mice bearing human subcutaneous infantile hemangioma.Results: The microspheres were of desired particle size (~77.8 µm) and drug encapsulation efficiency (~23.9%) and achieved sustained drug release for 40 days. PLIM exerted efficient inhibition of the proliferation of HemSCs and significantly reduced the expression of two angiogenesis factors (vascular endothelial growth factor-A [VEGF-A] and basic fibroblast growth factor [bFGF]) in HemSCs. Notably, the therapeutic effect of PLIM in hemangioma was superior to that of propranolol and PL in vivo, as reflected by significantly reduced hemangioma volume, weight, and microvessel density. The mean hemangioma weight of the PLIM-treated group was significantly lower than that of other groups (saline =0.28 g, propranolol =0.21 g, PL =0.13 g, PLIM =0.03 g; PLIM vs saline: P<0.001, PLIM vs propranolol: P<0.001, PLIM vs PL: P<0.001). The mean microvessel density of the PLIM-treated group was significantly lower than that of other groups (saline =40 vessels/mm2, propranolol =31 vessels/mm2, PL =25 vessels/mm2, PLIM =11 vessels/mm2; PLIM vs saline: P<0.001, PLIM vs propranolol: P<0.01, PLIM vs PL: P<0.05).Conclusion: Our findings show that PLIM is a very promising approach to locally and efficiently deliver propranolol to the hemangioma site leading to a significant inhibition of infantile hemangioma. Keywords: propranolol, liposomes, microsphere, controlled release, hemangioma